Inflammatory markers CRP and WBC as predictors of liver function impairment in multiple injury trauma patients: a repeated measures analysis - Wang, Gang; Tang, Cui; Wang, Rui; Xu, Chundao; Shen, Tugang; Li, Gaokai (Frontiers in Medicine, 2025)
AimsTo investigate the relationship between liver function indices (AST, ALT, GGT) and inflammatory markers (CRP, white blood cell count) in multiple injury patients at different time points post-trauma.MethodsWe retrospectively analyzed 114 patients with multiple injuries admitted to a tertiary trauma center in Zhejiang Province (January 2023–December 2024). AST, ALT, GGT, CRP, white blood cell count, NLR, and LMR were measured at admission, 24 h, and 72 h post-admission. Age, drinking history, BMI, and gender were included as covariates. Statistical analyses employed both crude and adjusted GEE models with gender subgroup analysis.ResultsElevated CRP levels significantly correlated with increased AST (OR = 2.17, 95% CI: 1.14–4.12, p = 0.019) and ALT (OR = 2.37, 95% CI: 1.22–4.63, p = 0.011). The 72 h time point independently predicted ALT elevation (OR = 2.24, 95% CI: 1.37–3.65, p < 0.001). NLR (OR = 0.94, 95% CI: 0.90–0.99, p = 0.014) and WBC count (OR = 1.89, 95% CI: 1.12–3.18, p = 0.017) significantly predicted GGT elevation. Gender-stratified analysis revealed distinct patterns: In females, CRP elevation (both ≥40 mg/L and 10–40 mg/L) was inversely associated with AST (p < 0.05), and higher WBC correlated with lower GGT (B = –0.636, p = 0.017). In males, higher WBC was associated with lower AST; ALT decreased at 24 h (B = –1.08, p < 0.001) and 72 h (B = –1.11, p < 0.001); CRP 10–40 mg/L inversely correlated with ALT (B = –0.882, p = 0.008); and both higher WBC (B = –0.812, p = 0.013) and NLR (B = –0.063, p = 0.013) predicted lower GGT.ConclusionCRP and white blood cell count significantly correlate with liver function changes in multiple injury patients, with marked gender-specific differences in these associations. These findings suggest the need for sex-specific monitoring strategies in trauma-related hepatic dysfunction.